The effect of fraud or deception as one of the reasons for requesting a retrial in Jordanian law - Al-Hilalat, Muhammad Ali; Abu Hilal, Ibrahim Mudhi; Al-Rawashdeh, Muhammad Hussain (Journal of Economic, Administrative and Legal Sciences, 2022)
The request for a retrial due to the presence of fraud or deception, which is presented by the opponent in whose favor the judgment was not issued in the judicial case, is one of the unusual methods of appeal that the legislator stipulated exclusively, as the reasons for the request for a retrial should contribute to changing the judge’s conviction and affect The course of the lawsuit so that if it had been presented during the consideration of the lawsuit, the case or lawsuit would have gone to another path, and decided contrary to what it ruled. Studying the reasons for retrial and studying the legal framework regulating it by studying fraud as one of the reasons for retrial and clarifying the conditions that must be met to accept the challenge to retrial in form and substance. Stopping what was dealt with in the Code of Civil Procedure, as it dealt with cases directly in the first clause of Article 213 of the Code of Civil Procedure, and then dealt with other cases that may be considered such as Fraud and trick, which is (false testimony, produced papers, false oath, and incorrect representation). The researcher hopes to amend the text of Article (213) of the Code of Civil Procedure and to limit the cases that are considered as fraud in that case.